2018
DOI: 10.1016/j.redox.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

A reciprocal relationship between reactive oxygen species and mitochondrial dynamics in neurodegeneration

Abstract: Mitochondrial fragmentation due to fission/fusion imbalance has often been linked to mitochondrial dysfunction and apoptosis in neurodegeneration. Conventionally, it is believed that once mitochondrial morphology shifts away from its physiological tubular form, mitochondria become defective and downstream apoptotic signaling pathways are triggered. However, our study shows that beta-amyloid (Aβ) induces morphological changes in mitochondria where they become granular-shaped and are distinct from fragmented mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 76 publications
7
84
1
Order By: Relevance
“…TICAE and TICAE-ROSI cells had similar mitochondrial areas per cell in the sham condition, but it increased in irradiated TICAE-ROSI cells. Mitochondrial circularity was statistically different between the cell types and treatment conditions, of which high mitochondrial circularity is associated with a high redox stress state (Ahmad et al, 2013;Hung et al, 2018).…”
Section: Irradiation Triggers Mitochondrial Remodeling In Endothelialmentioning
confidence: 95%
“…TICAE and TICAE-ROSI cells had similar mitochondrial areas per cell in the sham condition, but it increased in irradiated TICAE-ROSI cells. Mitochondrial circularity was statistically different between the cell types and treatment conditions, of which high mitochondrial circularity is associated with a high redox stress state (Ahmad et al, 2013;Hung et al, 2018).…”
Section: Irradiation Triggers Mitochondrial Remodeling In Endothelialmentioning
confidence: 95%
“…Interestingly, studies investigating mitochondrial network dynamics have found that the state of mitochondrial morphology, whether fused or fragmented, has a direct consequence on all of the above-mentioned mitochondrial functions. Mitochondrial dynamics themselves undergo alterations with age [20][21][22][23][24][25]. Studies in nematodes [26], flies [27], and mice [28] have shown that the mitochondrial network of aged animals is often more heterogeneous, fragmented, and comprised of large, swollen mitochondria that cannot be eliminated by mitophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Fragmented mitochondria can be degraded selectively by mitophagy to protect the cell from apoptosis. Granular (fragmented) mitochondria are linked to high levels in ROS, and tubular (filamentous) mitochondria are inversely proportional to ROS level in neurodegeneration [73]. During mitosis, the question of whether fragmented mitochondria produce H 2 O 2 more than filamentous mitochondria should be addressed.…”
Section: Source For H 2 O 2 Generation Throughout the Cell Cyclementioning
confidence: 99%